The effect of premium income, expenses claim, and underwriting on profitability of Indonesia joint enterprises insurance companies - Markonah Markonah; Hedwigis Esti Riwayati; Riska Kumalasari (Jurnal Siasat Bisnis, 2023)
Purpose – This research has purposes to scrutinize over the role of premium income, expenses claim and underwriting results towards profitability of Indonesia Joint Enterprises Insurance Companies. Design/methodology/approach – The sample used is general insurance company that presents complete financial statements during 2018-2021 and listed by Otoritas Jasa Keuangan through its official website. Purposive sampling used as sampling technique with several samples are 48 data. Panel data regression used as analysis technique which then processed by Eviews-9 application. Findings – Its results showed that only underwriting results which significantly affect on profitability, while the others variables such as premium income had significantly negative affect on profitability so did with the expense claims which turn out had no affect towards profitability. At the level of significance (α = 0.05), it has small effect, while at the significance level of (α = 0.10), the expense claims seem had significant negative affect on profitability of Indonesia general insurance industry. Research limitations/implications – This research has certainly limitations such as the research object used relatively small only the joint general insurance companies which submitted complete financial reports which are listed by Otoritas Jasa Keuangan and followed by the company’s official website. Practical implications – This research indicates that those companies are noticed about an increase in premiums, but on the other hand they have also received many claims, therefore those premiums will be diverted to finance the claims which occur lately, then this certainly would decrease an income or profitability of the insurance company itself. Originality/value – This research also has a different research object and research period compared to previous research, therefore it can be used as a complement the research which have done before.